Morphology genetic 3D hierarchical SnO2 microstructures constructed by Sub 5 nm nanocrystals for highly sensitive ethanol-sensor. (7th September 2021) - Li, Wenqian; Yan, Changyu; Zhu, Yuedan; Tian, Heng; Hu, Jinhai; Iqbal, Asma; E, Peisan; Zai, Jiantao; Qian, Xuefeng
Abstract: SnO2 is widely used for ethanol-sensing applications due to its excellent physicochemical properties, low toxicity and high sensitivity. However it is a challenge to construct 3D-hierarchical structures with sub 5 nm primary grain particle, which is the optimized size for ethanol sensor. Herein, genetic tri-level hierarchical SnO2 microstructures are synthesised by the genetic conversion of 3D hierarchical SnS2 flowers assembled by ultrathin nanosheets. The SnS2 nanosheets are morphology genetic converted to porous nanosheets with sub 5 nm SnO2 nanoparticles during the calcination process. When used for the detection of ethanol, the sensor exhibits a high sensitivity of 0.5 ppm ( R a / R g  = 6.8) and excellent gas-sensing response ( R a / R g = 183 to 100 ppm) with short response/recovery time (12 s/11 s). The excellent gas sensing performance is much better than that of the previous reported SnO2 -based sensors. The highly sensitivity is attributed to the large surface area derived from the recrystallization and volume changes, which offers more active sites during the morphology genetic conversion from SnS2 to SnO2 . Furthermore, the flower-like 3D structure enhances the stability of the materials and is beneficial for the mass diffusion dynamics of ethanol.